Modeling and evaluation of performance of dual field-of-view common-aperture dual-band imaging system - Wang, Qingsong; Gao, Ming (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
For the modeling and evaluation of dual field-of-view (FOV) common-aperture dual-band imaging system performance, two factors must be considered at the same time. One is that the system must have a larger target acquisition range, and the other is that the detection range and recognition range of the system must be the same. In this paper, taking the dual FOV common-aperture visible/long-wave infrared (LWIR) imaging system as an example, the performance of the dual FOV common-aperture dual-band imaging system is modeled and evaluated using an imaging system performance model based on comprehensive resolution. Firstly, the target acquisition range of the dual FOV visible imaging system is analyzed, and the condition that the detection range is equal to the recognition range is obtained. Then, under the condition of common aperture, the target acquisition range and the relationship between detection range and recognition range of dual FOV LWIR imaging system are analyzed. The analysis results show that, under the condition of dual FOV and common aperture, when the detection and recognition ranges of the visible imaging system are equal, the detection and recognition ranges of the LWIR imaging system are not equal. When the detection and recognition ranges are close by reducing the comprehensive resolution, the target acquisition range of the dual FOV common-aperture dual-band imaging system will decrease.
Optica Applicata, Vol. 52, 2022, nr 4, s. 535-550
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; common-aperture; dual-band; dual FOV; performance modeling